2021
DOI: 10.1002/jmv.26880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combination of nitazoxanide, ribavirin, and ivermectin plus zinc supplement (MANS.NRIZ study) on the clearance of mild COVID‐19

Abstract: This trial compared the rate and time of viral clearance in subjects receiving a combination of nitazoxanide, ribavirin, and ivermectin plus Zinc versus those receiving supportive treatment. This non-randomized controlled trial included 62 patients on the triple combination treatment versus 51 age-and sex-matched patients on routine supportive treatment. all of them confirmed cases by positive reverse-transcription polymerase chain reaction of a nasopharyngeal swab. Trial results showed that the clearance rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 51 publications
(103 reference statements)
3
52
0
6
Order By: Relevance
“…This has the potential to mask the effects of proxalutamide or to introduce imbalances in the application of usual care medication. However, in the usual care treatment, only nitazoxanide has been shown to have potential efficacy in placebo-controlled trials (29)(30)(31) and this drug was offered to all new patients. Further, the randomization of patients to each trial study arm would mitigate any uneven distribution of usual care medications, if they existed.…”
Section: Discussionmentioning
confidence: 99%
“…This has the potential to mask the effects of proxalutamide or to introduce imbalances in the application of usual care medication. However, in the usual care treatment, only nitazoxanide has been shown to have potential efficacy in placebo-controlled trials (29)(30)(31) and this drug was offered to all new patients. Further, the randomization of patients to each trial study arm would mitigate any uneven distribution of usual care medications, if they existed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more studies should be done in this field. It has recently been shown that the combination of nitazoxanide, ribavirin, ivermectin, and zinc supplementation has a significant effect on clearing the SARS-COV2 [ 156 ]. A limited number of studies have been performed on the importance of anti-viral zinc-dependent proteins in SARS-COV2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from being regarded as a broad-spectrum antiviral agent against DNA and RNA, which can obstruct viral messenger RNA binding RNA-dependent RNA polymerase production (RpRd), it is also a prodrug that metabolizes into nucleoside analogues that block viral RNA and capping viral mRNA. The combination of nitazoxanide, ribavirin, and ivermectin, as well as zinc supplementation, removed SARS-CoV-2 from the nasopharynx faster than symptomatic treatment ( 155 ).…”
Section: Therapeutics Strategiesmentioning
confidence: 99%